2017
DOI: 10.1016/j.epsl.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Regional changes in streamflow after a megathrust earthquake

Abstract: Moderate to large earthquakes can increase the amount of water feeding stream flows, mobilizing excess water from deep groundwater, shallow groundwater, or the vadose zone. Here we examine the regional pattern of streamflow response to the Maule M8.8 earthquake across Chile's diverse topographic and hydro-climatic gradients. We combine streamflow analyses with groundwater flow modelling and a random forest classifier, and find that, after the earthquake, at least 85 streams had a change in flow.Discharge mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 50 publications
1
86
0
Order By: Relevance
“…Our findings thus favor a binary response, that is, that streamflow changes occur if ground motion is large enough, but the magnitude of response is independent of the ground motion beyond the threshold. A previous study was unable to identify hydrogeological, tectonic, or land cover controls (Mohr et al, 2017). Similarly, Cox et al (2015) report a threshold for PGA of 0.5% g for springs in New Zealand to respond to earthquakes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our findings thus favor a binary response, that is, that streamflow changes occur if ground motion is large enough, but the magnitude of response is independent of the ground motion beyond the threshold. A previous study was unable to identify hydrogeological, tectonic, or land cover controls (Mohr et al, 2017). Similarly, Cox et al (2015) report a threshold for PGA of 0.5% g for springs in New Zealand to respond to earthquakes.…”
Section: Discussionmentioning
confidence: 94%
“…PGVs provided by ShakeMap combine the maximum value observed on the two horizontal components of motion. We do not compare responses with static volumetric strains because a previous analysis of the response to the 2010 M8.8 Maule earthquake and studies elsewhere found no general correlation between the sign of the volumetric strain and the sign of the discharge change (e.g., Mohr et al, 2017). We do not compare responses with static volumetric strains because a previous analysis of the response to the 2010 M8.8 Maule earthquake and studies elsewhere found no general correlation between the sign of the volumetric strain and the sign of the discharge change (e.g., Mohr et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism causing both sustained negative and positive hydraulic changes is frequently related to static stress modifications evidenced by comparison between pre-seismic and post-seismic conditions (Jonsson et al 2003;Montgomery and Manga 2003;Parvin et al 2014;Mohr et al 2016). The difference between transient dynamic oscillations (Cooper et al 1965) and the offset-type Fig.…”
Section: Discussionmentioning
confidence: 99%